Longing to tell : Black women talk about sexuality and intimacy - Rose, Tricia (New York : Farrar, Straus and Giroux, 2003)
"In this book, Tricia Rose breaks the silence by presenting, for the first time, the in-depth sexual testimonies of black women. Spanning a broad range of ages, levels of education, and socioeconomic backgrounds, nineteen women, in their own words, talk with startling honesty about sex, love, family, relationships, body image, and intimacy. Their moving stories provide revealing insights into the many ways black women navigate the complex terrain of sexuality. Compelling, surprising, and powerful, Longing to Tell is sure to jump-start a dialogue and will be required reading for anyone interested in issues of race, gender, and sexuality."--Jacket.
Foreword -- Acknowledgments -- Introduction -- 1. Through the fire -- Sarita -- Luciana -- Rita -- Linda Rae -- Joclyn -- Amparo -- Cocoa -- 2. Guarded heart -- Soupe -- Audrey -- Pam -- Diane -- Aracely -- Carliese -- 3. Always something left to love -- Rhonda -- Anondra -- Millie -- Gloria -- Veronica -- Queenie -- Shanice -- Epilogue -- Afterword : the past as prologue -- Notes -- Selected bibliography -- Index.
Includes bibliographical references (pages 403-404) and index.
Keywords: African American women -- Psychology; United States -- Race relations -- Psychological aspects; interviews; Interviews; Interviews; Interviews